Digital means and their impact on financial inclusion in Iraqi banks (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research addressed the impact of digital means on financial inclusion in Iraqi banks, and the use of these programs in managing financial transactions and providing various financial services such as payments, lending, credit, and others. Through this research, we will shed light on the basic concepts about financial digital technology as an introduction to the topic, Its impact on the development of the famous political trend through the digital services provided, their comprehensive subscriptions, and the general transformations in the technological field that attract the provision of diverse and appropriate services. Descriptive and analytical material was used to study the research phenomenon. It  resorted to using one of the statistical methods (the logistic model) in the practical aspect of the research to compare the best banking methods for a number of Iraqi banks in Baghdad (digital and traditional means and finding the degree of compatibility between them). The research reached a number of results, the most important of which is that the statistical model used classified 75% of the bankers. They prefer to adopt both digital and traditional means as an advanced and modern way of working.